2017
DOI: 10.1038/ncomms15420
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic diversity of synthetic supramolecular polymers in water as revealed by hydrogen/deuterium exchange

Abstract: Numerous self-assembling molecules have been synthesized aiming at mimicking both the structural and dynamic properties found in living systems. Here we show the application of hydrogen/deuterium exchange (HDX) mass spectrometry (MS) to unravel the nanoscale organization and the structural dynamics of synthetic supramolecular polymers in water. We select benzene-1,3,5-tricarboxamide (BTA) derivatives that self-assemble in H2O to illustrate the strength of this technique for supramolecular polymers. The BTA str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 38 publications
8
72
0
Order By: Relevance
“…[24] Remarkably,t he exchange dynamics of both monomers are slowed down upon copolymerization, ar esult that is seconded by molecular dynamics simulations. We apply hydrogen-deuterium exchange mass spectrometry (HDX-MS) to monitor the exchange dynamics of supramolecular polymers and copolymers,asithas recently been proved to be apowerful label-free method to elucidate dynamic processes in supramolecular polymers.…”
mentioning
confidence: 87%
“…[24] Remarkably,t he exchange dynamics of both monomers are slowed down upon copolymerization, ar esult that is seconded by molecular dynamics simulations. We apply hydrogen-deuterium exchange mass spectrometry (HDX-MS) to monitor the exchange dynamics of supramolecular polymers and copolymers,asithas recently been proved to be apowerful label-free method to elucidate dynamic processes in supramolecular polymers.…”
mentioning
confidence: 87%
“…From the 1 HNMR spectrum of BTTPAi n[ D 6 ]DMSO with D 2 O ( Figure S7), the protonp eak of amide bonds cannotb ed etected because of the H-D exchange, suggesting water contacted with the amide bonds and may influence the packing. [23] Based on the optimized results (Scheme S2), at high water content, the BTTPAd imer was stabilized by water molecules through NÀH···O and OÀH···O hydrogen bonds, and an overlapped structure was obtained. However,a tl ow water content, there are too few water molecules available to form sufficient numberso fh ydrogen bonds to sustain such overlapped structure, leading to as lipped structure.…”
Section: Packing Modes In the Gel Statementioning
confidence: 99%
“…Such a structural and dynamic diversity within fiber (2) is consistent with recent experimental and computational observations that revealed that these water-soluble assemblies are way more dynamic and less ordered than expected. 21,32 On the other hand, fiber (1) appears as a nearly perfect stack of monomers (similar to the cartoons of ideal fibers often used in the literature).…”
Section: Automatic Comparison Of Defects In Different Supramolecular mentioning
confidence: 84%